Knowledge and willingness of schoolteachers in Jordan to perform CPR: a cross-sectional study - Ahmad Alrawashdeh; Alaa O Oteir; Mahmoud T Alwidyan; Zaid I Alkhatib; Eihab A Khasawneh; Zainab Alqudah; Suha A Albataineh; Yamen Abukheat (BMJ Open)
Objectives This study aimed to assess the cardiopulmonary resuscitation (CPR) knowledge and willingness of schoolteachers in Jordan.Design This was a cross-sectional study conducted using an online questionnaire.Setting For inclusion in this study, schoolteachers must be currently teaching at any level in schools across the country. Responses were collected from 1 April 2021 to 30 April 2021.Participants All schoolteachers actively working in public or private schools were included in our study.Primary and secondary outcome measures Continuous variables were summarised as means and SD, whereas categorical variables were reported as frequencies and percentages (%). A χ2 test for independence, independent sample t-tests and analysis of variance were used appropriately. A p-value less than 0.05 was used to determine statistical significance.Results A total of 385 questionnaires were eligible for analyses. Only 14.5% of the participants received CPR training and overall correct knowledge answers were 18.8% of the total score. Those participants with previous CPR training had higher mean knowledge scores (2.34 vs 1.15, p<0.001). Trained participants were also more likely to provide hands-only CPR to various patient groups than untrained participants (p<0.05). Participants were more willing to provide standard CPR to family members than hands-only CPR (p<0.001), but more willing to provide hands-only CPR to friends (p<0.001), students (75.1% vs 58.2%, p<0.001), neighbour (p<0.001), stranger (p=0.001) and patient from the opposite gender (p<0.001).Conclusions Schoolteachers in Jordan possess limited knowledge of CPR. However, the study participants showed a positive attitude towards performing CPR. The study revealed that they were more inclined to provide hands-only CPR than standard CPR. Policymakers and public health officials can take advantage of these findings to incorporate CPR training programmes for schoolteachers, either as a part of their undergraduate studies or as continuing education programmes with an emphasis on hands-only CPR.